Patient safety in hemotransfusion: a bibliometric review (Research, Society and Development, 2021)
This research aims to identify, through bibliometric studies, how the scientific production on patient safety during blood transfusion takes place. This is a bibliometric review with a descriptive approach, using the Web of Science database, and for descriptive analysis the VOSviewer software was used, considering the articles published in the last five years (2017-2021). The author with the highest number of articles published was Delaney, meghan, with 19 articles published and the most recent is from 2020, the journal with the highest number of articles was the journal Transfusion with 54 publications and the term “transfusion” was characterized as the central concept of publications. It is concluded that the related analyzes of the authors allowed us to know the authors who publish the most articles, the journals were able to know their productions and the analysis of the keywords acquired by VOSviewer made it possible to know the main ones related to the exposed theme.